Architectural overview of the SPEAKeasy system. - Cook, P.G.
SPEAKeasy is a successful implementation of a software-defined radio (SDR) for military applications. It permits general-purpose digital hardware to communicate over a wide range of frequencies, modulation techniques, data encoding methods, cryptographic types, and other communication parameters. The background of SDRs for military and commercial needs is discussed, and the SPEAKeasy architecture is defined
Keywords: SPEAKeasy system; Architectural overview; Communication parameters; Cryptographic types; Data encoding methods; General-purpose digital hardware; Hardware architecture; Military applications; Modulation techniques; Software architecture; Software-defined radio